Effect of Glycerol Concentration and Filler Addition on the Properties of Bioplastics Derived from Kepok Banana Corm Starch - Nasution, Halimatuddahliana; Manurung, Budi Holfrid; Nofifah, Nofifah (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2025)
The waste from kepok banana corms and stems has not been well utilized, even as banana production continues to rise, increasing the volume of such waste. In Indonesia, banana production in 2023 reached 9.75 million tons, up from 7.2 million tons the previous year, leading to a corresponding increase in banana waste. This research investigates the effects of glycerol and banana stem filler on the properties of bioplastics made from kepok banana corm starch, aiming to develop a sustainable alternative to conventional plastics. Starch was extracted from kepok banana corms through grinding, filtering, and drying at 80C for 15 minutes. Cellulose filler was produced from banana stems using bleaching with NaOH and H2O2, followed by neutralization and drying to a constant weight. Bioplastics were then produced with filler concentrations of 0%, 2%, 4%, and 6% and glycerol volumes of 1-4 mL per 10 grams of starch, on mixing conducted at 70C in distilled water. Characterizations and tests of the bioplastics included for cristallinity, functional groups, surface morphology, yield, density, water absorption, tensile strength, and elongation. Bioplastics with addition filler performed better than those without filler, with the 6% filler and 2 mL glycerol variation showing the most favorable properties, including a yield of 25.92%, density of 1.14 g/mL, water absorption of 0.24%, tensile strength of 5.49 MPa, elongation of 8%, and a homogeneous surface with well-distributed filler. These findings demonstrate the potential of kepok banana waste-based bioplastics as an environmentally friendly alternative.